Incorporation of phase change materials into building envelope for thermal comfort and energy saving: A comprehensive analysis - Al-Yasiri, Qudama; Szabó, Márta (Journal of Building Engineering, 2021)
Building envelope is a key element in providing adequate energy and thermal comfort performance to buildings. In this regard, improvement solutions are implemented in recent studies that focus on new techniques and methods. The main techniques adopted in this context are discussed to identify modern and effective methods with a particular focus on phase change materials (PCMs). Incorporating PCMs with building construction materials is a booming technology, owing to their enhancement potential of storing and releasing heat during phase transition. This work highlights the importance of PCMs in building envelope, focusing on roof and external wall applications. PCM types, general and desired properties and application area are presented and discussed. Influential parameters, incorporation techniques and methods, main numerical tools, and modelling equations are used to describe the thermal behaviour of PCM. A comprehensive assessment on the basis of recent studies has been conducted to point out the potential of PCM with the most appropriate techniques under different locations. The main findings of PCM thermal performance have been described, considering the cooling/heating load reduction, energy-saving and thermal comfort gained along with several research hiatuses for future studies. •PCMs incorporated building envelope related research in recent years are reviewed.•The advantages of PCM in buildings based on energy-saving and thermal comfort are discussed.•PCM types, properties, influential parameters, incorporation techniques and modelling are presented and analysed.•A comprehensive assessment of PCM incorporated construction materials is highlighted.•Main findings in the literature and research gaps are identified.